Beware the power of the dark side! : an original retelling of Star Wars: Return of the Jedi - Angleberger, Tom (Disney/Lucasfilm Press, 2015)
Presents a retelling of the third Star Wars movie, featuring Luke Skywalker, Han Solo, and Princess Leia as they battle the Empire. The evil Empire is constructing a second Death Star to crush the Rebel Alliance. But Luke Skywalker has other plans-- to destroy the Empire and stop the Emperor once and for all. Yet there is one thing standing in his way... his father.